High photoluminescence intensity of heterostructure AlGaN-based DUV-LED through uniform carrier distribution - Hairol Aman, Mohammad Amirul; Ahmad Fajri, Faris Azim; Ahmad Noorden, Ahmad Fakhrurrazi; Daud, Suzairi; Bahadoran, Mahdi; Abdul Kadir, Muhammad Zamzuri (IOP Publishing, 2023)
We report a numerical analysis of the variation of Aluminium (Al) composition in Al Gallium Nitride (AlGaN)-based Deep-Ultraviolet Light-Emitting Diode (DUV-LED) and its effects on the carrier concentration, radiative recombination, and photoluminescence (PL). Three different structures with different Al compositions are compared and analyzed. The radiative recombination of the DUV-LED is less efficient due to the imbalance of carrier distribution. The findings show that the uniform electrons and holes distribution significantly improve the radiative recombination for structure with a thin step-shaped quantum well (QW). The simulated structure emits a wavelength of 302.874 nm, categorized in the ultraviolet-B (UV-B) spectrum. Our results imply that carrier uniformity in QW is required to enhance the light intensity of DUV-LED. Remarkably, the uniformity enhances the PL intensity drastically, at least six times higher than the first structure and twice higher than the second structure.